A Comparison of Pain between Parkinson’s Disease and Multiple System Atrophy: A Clinical Cross-Sectional Survey - He-Yang You; Lei Wu; Hai-Ting Yang; Chen Yang; Xiao-Ling Ding (Pain Research and Management)
Background. Pain is frequent in Parkinson’s disease (PD) and Parkinson-plus syndrome. This study aimed to assess the prevalence, characteristics, therapy (especially the effect of dopaminergic therapy), and associated symptoms of pain in Parkinson's disease and multiple system atrophy (MSA) patients. Methods. Seventy-one PD patients, sixty-five MSA patients, and forty age-matched healthy controls were enrolled and evaluated by using the German pain questionnaire and visual analogue scale (VAS). In addition, the influence of pain in PD patients on anxiety, depression, and the quality of life was assessed with the Hospital Anxiety and Depression Scale (HADS) and Parkinson’s Disease Questionnaire (PDQ-39). Results. Compared to that of the healthy controls, the PD and MSA patients had a significantly higher presence of pain (P<0.01, P<0.01). PD patients had a higher presence of pain than MSA patients (P=0.007). No difference in VAS scores was observed between the PD and MSA patients (P=0.148). A total of 21 PD patients (42.85%) with pain and 13 MSA patients (43.33%) with pain received treatment. A total of 13 PD patients with pain and 6 MSA patients with pain had an improved pain intensity after using dopaminergic medication. The differences in the disease duration, Hoehn and Yahr stages, and scores on the Unified Parkinson’s Disease Rating Scale motor score, HAD-D, HAD-A, and PDQ-39 were significant between the PD patients with and without pain. Conclusion. PD and MSA patients are prone to pain with insufficient treatment. Pain interventions should be provided as soon as possible to improve the patient’s life.